Childhood maltreatment correlates with higher concentration of transforming growth factor beta (TGF-β) in adult patients with major depressive disorder. (July 2021) - Jovanovic, Ana Munjiza; Mitkovic-Voncina, Marija; Kostic, Milutin; Jeremic, Marija; Todorovic, Jovana; Popadic, Dusan; Tosevski, Dusica Lecic; Markovic, Ivanka
Highlights: Depression and childhood maltreatment (CM) history inter-correlate. Higher TGF-β levels correlate both with depression and CM history. TGF-β levels are higher in depression with CM history compared to depression alone. Depression potentiates the effect of CM history on the blood TGF-β levels. Abstract: Transforming growth factor beta (TGF-β), which has a role as a regulatory cytokine, has not been widely investigated in patients with major depressive disorder (MDD) who experienced childhood trauma. The aim of our study was to investigate the differences in circulating TGF-β levels between the patients with major depressive disorder (MDD) with and without child maltreatment (CM) history, and to compare them to the corresponding control subjects' groups (with or without CM). Blood samples were obtained from 55 patients, fulfilling DSM-IV-R criteria for a current MDD episode without psychotic symptoms, and 45 healthy controls, matched for age and gender. Participants were administered the Childhood Trauma Questionnaire (CTQ). Serum TGF-β concentration was determined by enzyme-linked immunosorbent assay. The concentration of TGF-β was significantly higher in patients with MDD with CM history, compared to MDD patients with no CM, as well as both control groups. Furthermore, we have shown that the combined effect of CM history and MDD affected TGF-β levels in adulthood, which was not observed in the control group with CM. These results indicate that MDD patients with the experience of CM have altered immune-regulatory response, and they may constitute a specific subtype within this heterogenic disorder (ecophenotype).